2022
DOI: 10.1007/s10163-022-01486-7
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of crushed concrete and steel slag in drainage structures of geotechnical works and road pavements

Abstract: A crushed concrete aggregate, processed from construction and demolition waste and a siderurgical aggregate, processed from electric arc furnace steel slag, were selected based on their very high availability worldwide and known technical feasibility to be used in construction works. Given the association of their presence to the possibility of reducing the drainage capacity of unbound granular layers of road pavements and drainage structures which they may be associated with, there are studies and regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Experimental studies have indicated that steel slags have the potential to be a suitable replacement for natural aggregates typically used in road filling [5,11,26,[67][68][69] and have sufficient drainage capability [70], resulting in improved performance as the ratio of fine content decreases [71]. However, toxic trace metals released due to high alkalinity cause environmental damage.…”
Section: The Ph/ec Results Of Eaf and Ls By Swltsmentioning
confidence: 99%
“…Experimental studies have indicated that steel slags have the potential to be a suitable replacement for natural aggregates typically used in road filling [5,11,26,[67][68][69] and have sufficient drainage capability [70], resulting in improved performance as the ratio of fine content decreases [71]. However, toxic trace metals released due to high alkalinity cause environmental damage.…”
Section: The Ph/ec Results Of Eaf and Ls By Swltsmentioning
confidence: 99%